‘What is your orthography like?’ An essay on Polish spelling up to the mid-19th c. - Makarewicz, Renata (Papers in Linguistics, 2022)
The article primarily concerns an approach to the core of conventionalised rules of spelling contained within the pronouns twoja (‘your(s)’) and nasza (‘our(s)’). The former symbolises a convention reached by a single person, usually the author of the published rules of spelling him- or herself. The latter is plural, which suggests that the convention was agreed upon by multiple persons, and thus, the published spelling should also be used by multiple persons. The aim of this article is to prove that Polish orthography only truly began after the 1830 publication of Rozprawy i wnioski o ortografii polskiej (‘Studies and Conclusions Regarding Polish Orthography’). The article takes an essay form and describes the situation in Polish spelling before the publication of Rozprawy i wnioski, which is a collection of theoretical articles written by the authorities of that period. The article also discusses the role that the dictionary edited by Samuel Bogumił Linde played in solidifying a single model of spelling of the registered lexemes. Furthermore, it provides short biographies of the authors of each study included in Rozprawy i wnioski and an overview of the core arrangements regarding non-conventionalised spelling. Each section of the article includes a commentary of its author.